1976
DOI: 10.1080/00365517609054490
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate- and Aspirin-Induced Uncoupling of Oxidative Phosphorylation in Mitochondria Isolated from the Mucosal Membrane of the Stomach

Abstract: The hypothesis that the damaging effect on the stomach mucosa of salicylic acid and its derivatives is ascribable to an uncoupling of oxidative phosphorylation has been investigated by testing of mitochondria isolated from the corpus gland area of mini-pig gastric mucosa. Mitochondria, influenced by salicylate or acetylsalicylate (0.7-5.6 mmol/l), demonstrated increased respiration rate, decreased respiratory control ratio, and decreased P/O ratio when tested in vitro. Uncoupling of oxidative phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The impact of SA on mitochondrial function is not a cucumber-specific phenomenon. Similar uncoupling and inhibitory effects have also been reported in tobacco [67], soybean [68], Arabidopsis [69], and even in mammalian cells [70]. In Arabidopsis, SA directly acted on mitochondrial respiratory complex III and inhibited its activity [69].…”
Section: Discussionsupporting
confidence: 58%
“…The impact of SA on mitochondrial function is not a cucumber-specific phenomenon. Similar uncoupling and inhibitory effects have also been reported in tobacco [67], soybean [68], Arabidopsis [69], and even in mammalian cells [70]. In Arabidopsis, SA directly acted on mitochondrial respiratory complex III and inhibited its activity [69].…”
Section: Discussionsupporting
confidence: 58%
“…(24,25) The ATP deficiency and the accumulation of adenosine diphosphate (ADP) and adenosine monophosphate (AMP) stimulate glycolysis in enterocytes. (26) The maximally stimulated glycolysis induced the production of lactate rather than acelyl CoA, because pyruvate dehydrogenase activities are low in enterocytes.…”
Section: The Pathophysiology Of Nsaid-induced Small Intestinal Injuriesmentioning
confidence: 99%
“…Other studies also demonstrated importance of mitochondrial disorders by NSAIDs on their intestinal toxicity. (20,21) …”
Section: Nsaids-induced Small Bowel Injury and Mitochondrial Disordersmentioning
confidence: 99%